Impact of Online Discount on Indian Shoppers During Festive Seasons: An Analytical Study - Dr. Akshat Dubey, Dolly Tripathi, (European Economic Letters (EEL), 2024)
With the increasing preference of Indians to shop online instead of visiting physical stores, the retail sector in the country is undergoing significant transformation. Several factors are fueling the rapid rise in popularity of online shopping in India. These include the increasing internet penetration, a growing number of internet-savvy consumers, a larger labour force, a wide range of online stores offering goods from around the globe, and improved web accessibility. The concept of "e-tailing" refers to the business model where products are bought and sold through an online platform. India's retail sector is currently undergoing a significant transformation due to the transition from traditional stores to online marketplaces. During the festival season, online retailers are currently offering a variety of deals to attract more customers. In recent years, the popularity of online shopping has soared, allowing consumers to easily purchase a wide range of products, from everyday essentials to cutting-edge technology. Online shopping and digital shops are becoming increasingly popular in rural areas, reaching beyond the confines of city life. Several factors contribute to this phenomenon, such as increasing incomes, a stronger economy, a wide range of choices for consumers, and the active involvement of lenders in promoting digitalization and online shopping. The festival shopping sector is a significant driver behind the growth of e-commerce platforms. During holiday seasons, companies frequently offer promotions and significant discounts on both new and used products. In addition, they offer additional incentives such as cash-back deals and buy-one-get-one sales. At this time, companies would organise sales events with distinctive names such as "Big Billion Days" on Flipkart, "Flash Sales" on Myntra, and "Great Festive Sale" on Amazon. The aim of this study is to examine the impact of virtual shopping festivals on local communities and individual shoppers.